Faktor kejayaan dan kegagalan projek ICT di luar bandar - Omar, Siti Zobidah; Abu Hassan, Musa; Ismail, Narimah; Bolong, Jusang (Universiti Putra Malaysia Press, 2008)
The success and failure of ICT projects depends on how the relevant agency set the strategy to attract the local community to use the facility. The purpose of this paper is to identify factors that contributing to the success and failure of such project. This research is based on Technology Acceptance Model. The study involved 60 supervisors, 1250 participants and 716 non-participant of the rural ICT projects were interviewed to get their information regarding the issue. It was found that among the supervisors, they said that equipment is crucial for the success of rural ICT projects, followed by management, finance and support services. However, among the project participants, they mentioned that management as the important factor for the success of rural ICT projects, followed by equipment, finance and programs. With regard to factors that may lead to project failure, the supervisors identified equipment as the major factor, followed by finance, management and support services. Nevertheless, the project participants said that finance as an important factor to the failure of rural ICT projects, followed by equipment, management and support services. Thus, it can be said that there are not much different among the supervisors and the project participants in relation to the factors that contribute to the success or failure of rural ICT projects.